2010 Third International Conference on Software Testing, Verification, and Validation Workshops 2010
DOI: 10.1109/icstw.2010.33
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Obstacles to Test-Driven Learning on Day One

Abstract: Abstract-We describe the preliminary construction of a web-based tool for test-driven learning in the first weeks of programming. We discuss obstacles to test-driven learningboth pragmatic and ideological-and describe the ways that we believe our tool overcomes these obstacles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Prior studies have shown that TDL can be applied in entry level classes without removing current course material, and that students who try TDL, tend to like TDL [24]. However, prior to WebIDE, finding ways to enforce a test-driven approach with beginning programmers has proven to be elusive [9].…”
Section: Test-driven Learningmentioning
confidence: 99%
“…Prior studies have shown that TDL can be applied in entry level classes without removing current course material, and that students who try TDL, tend to like TDL [24]. However, prior to WebIDE, finding ways to enforce a test-driven approach with beginning programmers has proven to be elusive [9].…”
Section: Test-driven Learningmentioning
confidence: 99%
“…Unlike the systems above, WebIDE enables lab authors to create their own labs or use existing labs, and give specific student feedback on individual exercises. This functionality was explored and reported in an early prototype [15]. Although WebIDE may be seen as an alternative to some systems such as Turings Craft, it is intended to complement many systems such as Web-CAT and BlueJ (http://www.bluej.org).…”
Section: Introductionmentioning
confidence: 99%